Phenomenology Of Sound And Music In Horror Movies - Farkaš, Tomáš; Šurinová, Lenka (Communication Today, 2025)
The paper deals with the problem of effective and aesthetic exploitation of sounds, jangle, music and silence in making an atmosphere of stress and fear in horror movies. The authors analyze the frequency spectrum of sounds and complexity of musical motif in selected samples from two movies, which represent the minimalist and maxi-deal with relationship of audio and visual aspects of the movies explored. First part of the research is inspired by hypothesis of psychoacoustics dealing with physical characteristics of an unpleasant sound that causes intensive physiological reaction of a human organism. The authors assume that sound with these characteristics could be one of the reasons of an emotional reaction a viewer experiences when watching a horror movie. Next area on which this research is focused is the use of noises. According to psychoacoustics, noise affects the perception of other sounds, thus it is able to aid building of an atmosphere and tension in the movie. In the third part, the authors compare the complexity and variations of musical motifs of both of the movies. Motifs with lack of a structure and rigid repetitiveness can be boring for a viewer, which may be very counterproductive in terms of examined ﬁ lm genre. In the ﬁ nal part of this research, the authors deal with the relationship of audio and visual aspects of movies explored.